BdERECTA controls vasculature patterning and phloem-xylem organization in Brachypodium distachyon - Sakai, Kaori (BMC Plant Biol, 2021)
BACKGROUND: The vascular system of plants consists of two main tissue types, xylem and phloem. These tissues are organized into vascular bundles that are arranged into a complex network running through the plant that is essential for the viability of land plants. Despite their obvious importance, the genes involved in the organization of vascular tissues remain poorly understood in grasses. RESULTS: We studied in detail the vascular network in stems from the model grass Brachypodium distachyon (Brachypodium) and identified a large set of genes differentially expressed in vascular bundles versus parenchyma tissues. To decipher the underlying molecular mechanisms of vascularization in grasses, we conducted a forward genetic screen for abnormal vasculature. We identified a mutation that severely affected the organization of vascular tissues. This mutant displayed defects in anastomosis of the vascular network and uncommon amphivasal vascular bundles. The causal mutation is a premature stop codon in ERECTA, a LRR receptor-like serine/threonine-protein kinase. Mutations in this gene are pleiotropic indicating that it serves multiple roles during plant development. This mutant also displayed changes in cell wall composition, gene expression and hormone homeostasis. CONCLUSION: In summary, ERECTA has a pleiotropic role in Brachypodium. We propose a major role of ERECTA in vasculature anastomosis and vascular tissue organization in Brachypodium. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12870-021-02970-2.